Reconfigurable Silicon Photonic Processor Based on SCOW Resonant Structures - Liangjun Lu; Lin Shen; Wei Gao; Linjie Zhou; Jianping Chen (IEEE Photonics Journal)
Reconfigurable photonic processors, which can be programmed to perform multiple photonic processing tasks by using the same hardware platform, own the advantages of higher flexibility and more cost-effectiveness compared with application-specific photonic integration circuits (ASPICs). In this paper, we present a novel programmable photonic processor based on two-dimensional meshes of self-coupled optical waveguide (SCOW) resonant structures. The proposed processor can be configured for realizing various basic optical components, as well as cascaded and coupled components. As a proof-of-principle, we experimentally demonstrate the concept with a 3 × 1 SCOW-based processor on the silicon platform, including tunable couplers, variable optical attenuators, and phase shifters. We implement eight different configurations using the chip, including ring resonators, Mach-Zehnder interferometers, Fabry-Perot resonators, and composite structures built of these basic components. These results demonstrate that the proposed processor can be a promising candidate for multi-functional photonic processors.